Expression of the bcl-2 oncogene protein is not specific for the 14;18 chromosomal translocation. - Pezzella, F; Tse, A; Cordell, J; Pulford, K; Gatter, K; Mason, D (1990)
It has been reported previously that the bcl-2 protooncogene protein is detectable in neoplastic cells from cases of human lymphoma in which the 14;18 chromosomal translocation is present, but not in lymphomas that lack this chromosomal rearrangement or in normal lymphoid tissue. In the present study we confirmed, by immunohistologic labeling with polyclonal and monoclonal antibodies, that bcl-2 protein is strongly expressed in many cases of follicular lymphoma and that these neoplastic follicles differ clearly from their nonmalignant counterpart (reactive germinal centres) in which bcl-2 protein is undetectable. However we also found bcl-2 protein in normal T- and B-lymphoid cells and in a variety of lymphoproliferative disorders in which the 14;18 translocation is not present. It is therefore concluded that expression of bcl-2 protein is not a specific marker for lymphomas bearing the 14;18 chromosomal translocation and that the observations of other investigators may have reflected the inadequate sensitivity of their staining procedure.